Effects of gadoxetic acid on quantitative diffusion‐weighted imaging of the liver. Issue 2 (13th December 2012) - Colagrande, Stefano; Mazzoni, Lorenzo Nicola; Mazzoni, Elisa; Pradella, Silvia
<x xml:space="preserve">Abstract</x> Purpose To prospectively evaluate the effect of gadoxetic acid (Gd‐EOB‐DTPA; Primovist, Bayer‐Schering, Berlin, Germany) on quantitative diffusion‐weighted imaging (DWI) using the Le Bihan IntraVoxel Incoherent Motion model and considering separately the following parameters: slow diffusion coefficient (D), fast diffusion coefficient (D*), perfusion fraction (PF), and apparent diffusion coefficient (ADC). Materials and Methods Twenty‐four consecutive patients were submitted to the same magnetic resonance (MR)‐DWI acquisition before and after gadoxetic acid administration. Patients were divided into four groups according to the time at which the DW sequence was repeated, then 5, 10, 15, 20 minutes after contrast agent administration. A total of 48 manually drawn regions of interest (ROIs) of about 1200 pixels were placed in the middle right liver lobe. The mean and standard deviation (SD) were calculated in each group/patient for every DWI‐related parameter. Analysis of variance was performed (threshold P = 0.05). Bonferroni and Games‐Howell post‐hoc tests were applied if significant differences were found among groups; otherwise, data were averaged together. Results D, D*, PF, and ADC did not show any significant difference before and after contrast agent administration, at any time. Conclusion It is possible to perform DW acquisitions after gadoxetic acid administration without any significant variation of the values of DW‐related parameters under consideration in this study. J. Magn. Reson. Imaging 2013;38:365–370. © 2013 Wiley Periodicals, Inc.